2000
DOI: 10.1111/1467-646x.00058
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of Annual Report Releases and Market Reaction to Earnings Announcements in an Emerging Capital Market: The Case of China

Abstract: This paper examines the relation between firm performance and the timing of annual report releases in an emerging capital market. Based on the population of listed Chinese firms with A-shares for 1994-1997, we find that good news firms release their annual reports earlier than bad news firms, and loss firms release their annual reports the latest. Moreover, consistent with Chambers and Penman (1984) and Begley and Fischer (1998), these firms unexpectedly accelerate the release of good news and delay the disclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(81 citation statements)
references
References 14 publications
4
71
1
5
Order By: Relevance
“…The mean abnormal returns for firms with good news over the 12-month period are 18% for early announcements compared with 9.7% for late announcements. Our results are consistent with Haw et al (2000), who show that stock price reactions over the 12-month period are stronger for early announcements (23.4%) than for late announcements (18.2%). However, compared with the US market, the much smaller drift for the Chinese market still persists regardless of the timing of earning announcements.…”
Section: Timeliness Of Annual Earnings Announcementssupporting
confidence: 92%
See 2 more Smart Citations
“…The mean abnormal returns for firms with good news over the 12-month period are 18% for early announcements compared with 9.7% for late announcements. Our results are consistent with Haw et al (2000), who show that stock price reactions over the 12-month period are stronger for early announcements (23.4%) than for late announcements (18.2%). However, compared with the US market, the much smaller drift for the Chinese market still persists regardless of the timing of earning announcements.…”
Section: Timeliness Of Annual Earnings Announcementssupporting
confidence: 92%
“…To assess how the timeliness of annual earnings announcement affects the relation between earnings changes and stock returns in the Chinese market, we partition the sample (excluding the period 2007-2009) into two groups on the basis of the month when firms make their annual earnings announcement: early announcements are announcements made in January and February, and late announcements are announcements made in March and April. 6 Panel A of Table 9 indicates that the majority of firms (nearly 75%) do not make their annual earnings announcement until March or April regardless of whether they are announcing good news or bad news; this is consistent with Haw et al (2000). Interestingly, there are higher proportions of good news firms who release their annual earnings during the first 3 months than bad news firms.…”
Section: Timeliness Of Annual Earnings Announcementsmentioning
confidence: 60%
See 1 more Smart Citation
“…Numerous studies show mixed results in regards to the factors, which influence timeliness of submission the annual reports. Basu [14] and Haw et al [15] reveal that timeliness is directly related to the net profit earned by the company. The higher the profit, the more quickly one can expect the annual report to become publicly available.…”
Section: Introduction and Some Brief Literature Reviewmentioning
confidence: 99%
“…The higher the profit, the more quickly one can expect the annual report to become publicly available. Based on the information of listed Chinese firms with A-shares for 1994-1997, Haw et al [15] found that companies are willing to report good news, prepare and submit their annual reports earlier than companies with bad news, and companies with financial loss release their annual reports the latest. This is also confirmed by the findings of Han and Wild [16] showing that the timing of earnings reports has significant and far-reaching economic consequences.…”
Section: Introduction and Some Brief Literature Reviewmentioning
confidence: 99%